2008
DOI: 10.1590/s1516-35982008000300009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do uso de óleo de vísceras de aves oxidado na ração de frangos de corte sobre o desempenho, a composição da carcaça e a estabilidade oxidativa da carne da sobrecoxa

Abstract: Dietary oxidized poultry offal fat: performance, carcass and meat composition, and oxidative stability of frozen thigh meat of broiler chickens ABSTRACT -Two hundred male Ross broiler chicks were raised from 10 to 40 days of age and fed a corn-soy diet with 4% of fresh or oxidized poultry offal fat to evaluate the effects of dietary fat quality on broiler performance and on oxidative stability of frozen thigh meat during storage. Fresh poultry fat, characterized by low concentration of oxidation products deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
3
1
6
Order By: Relevance
“…However, the results obtained from Racanicci et al (2008) are different from those of the present study, in that by assessing the oxidized viscera oil effect on poultry performance, did not come by any difference in the performance when compared to poultry which received diets without oxidized viscera oil. Despite the existing difference between peroxide levels (Table 4) found and the level of inclusion in the feed, these same authors report that undesirable effects on performance are not always noted.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the results obtained from Racanicci et al (2008) are different from those of the present study, in that by assessing the oxidized viscera oil effect on poultry performance, did not come by any difference in the performance when compared to poultry which received diets without oxidized viscera oil. Despite the existing difference between peroxide levels (Table 4) found and the level of inclusion in the feed, these same authors report that undesirable effects on performance are not always noted.…”
Section: Resultscontrasting
confidence: 99%
“…All diets consisted of corn-based bran feed and soy bran, and sought to meet the needs of each age, following the specifications of Rostagno et al (2005). A pre-starter (from 1 to 7 days of age) feed was provided for all treatments and three starter (from 8 to 21 days of age) feeds provided according to the treatments (Table 1).…”
Section: Experimental Designmentioning
confidence: 99%
“…These values are in agreement with those obtained by Racanicci et al (2008) using the same samples tested here. The author obtained pH values from 6.07 to 6.34.…”
Section: Physical-chemical Analysissupporting
confidence: 92%
“…The global evaluation Racanicci et al (2008) showed that samples of chicken meat fed with different lipid sources and stored at −18 °C presented sufficient oxidative and organoleptic quality for consumption until 6 months. Probably, the difference in storage time compared to the present work (Table 5) can be attributed to the different animal feed and also to the freezing process employed.…”
Section: Sensory Characteristicsmentioning
confidence: 99%
“…Lin et al (1989) registraram uma redução significativa no peso ao abate e no peso das carcaças de frangos quando estes consumiram rações contendo óleo oxidado. Já Racanicci et al (2008) não observaram efeitos do fornecimento de alimentos oxidados sobre o desempenho de frangos de corte, porém registraram uma redução do rendimento do peito, que foi justificada pelo déficit energético da ração (cerca de 60 kcal/ kg) comprometendo a deposição de proteína muscular.…”
Section: Efeitos Da Utilização De Lipídios Oxidados Na Alimentação Anunclassified